2021
DOI: 10.1111/mcn.13129
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision‐making for infant feeding and care during the coronavirus disease 2019 pandemic

Abstract: Despite decades of research establishing the importance of breastfeeding, skin‐to‐skin contact and mother–infant closeness, the response to the coronavirus disease 2019 (COVID‐19) pandemic has underscored the hidden assumption that these practices can be dispensed with no consequences to mother or child. This article aims to support shared decision‐making process for infant feeding and care with parents and health care providers during the unprecedented times of the pandemic. It proposes a structure and ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 58 publications
(115 reference statements)
1
22
0
3
Order By: Relevance
“…Not only did no participants raise concerns about the potential risks of the interventions that they were offered, but the reduced opportunity for hands-on care means that conversations to establish informed consent are less likely to have occurred. This supports the findings of other studies of perinatal care during the pandemic, which have identified the lack of discussions between obstetric care providers and patients about the risks and potential outcomes of obstetric interventions as a major area of concern [ 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…Not only did no participants raise concerns about the potential risks of the interventions that they were offered, but the reduced opportunity for hands-on care means that conversations to establish informed consent are less likely to have occurred. This supports the findings of other studies of perinatal care during the pandemic, which have identified the lack of discussions between obstetric care providers and patients about the risks and potential outcomes of obstetric interventions as a major area of concern [ 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…31 Owing to COVID-19 restrictions, lactation support and maternity care practices supportive of breastfeeding have been significantly impacted. [32][33][34] To mitigate the spread and exposure to COVID-19, many hospitals, clinics, public health programs, and community-based organizations implemented very restrictive visiting policies. These restrictions eliminated critical birth and breastfeeding education, support, and community resources.…”
Section: Discussionmentioning
confidence: 99%
“…Frauen mit nachgewiesener oder vermuteter SARS-CoV-2-Infektion scheinen geringere Stillraten aufzuweisen [88]. Eine ausführliche Beratung und gemeinsame Entscheidungsfindung werden daher dringend empfohlen [89,90].…”
Section: Stillen Soll Bei Sars-cov-2-positiven Müttern Ermöglicht Und...unclassified